2013
DOI: 10.1186/1471-2393-13-119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elective cesarean section on the risk of mother-to-child transmission of hepatitis B virus

Abstract: BackgroundMany clinicians and hepatitis B virus (HBV)-infected pregnant women prefer elective caesarean section (ECS) to prevent mother-to-child transmission of HBV, since some studies found higher transmission of HBV in infants born by vaginal delivery (VD) than by cesarean section. However, other studies showed that ECS does not reduce the risk of being infected with HBV in infants. In this study, we aimed to clarify whether ECS may reduce the risk of mother-to-child transmission of HBV.MethodsTotally 546 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 18 publications
1
23
2
7
Order By: Relevance
“…However, other studies report no benefi t to elective cesarean section ( 106 ). Data from Beijing of 1,409 infants born to HBsAg-positive mothers from 2007 to 2011, all of whom received appropriate immunoprophylaxis at birth, reported MTCT rates of 1.4% with elective cesarean section compared with 3.4% with vaginal delivery and 4.2% with urgent cesarean section ( P <0.05) ( 107 ). When mothers in this study were stratifi ed according to HBV DNA, in those with low HBV DNA (<1,000,000 copies/ml or 2×10 5 IU/ml), delivery modality did not impact MTCT.…”
Section: Active-passive Immunoprophylaxis With Hepatitis B Immunementioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies report no benefi t to elective cesarean section ( 106 ). Data from Beijing of 1,409 infants born to HBsAg-positive mothers from 2007 to 2011, all of whom received appropriate immunoprophylaxis at birth, reported MTCT rates of 1.4% with elective cesarean section compared with 3.4% with vaginal delivery and 4.2% with urgent cesarean section ( P <0.05) ( 107 ). When mothers in this study were stratifi ed according to HBV DNA, in those with low HBV DNA (<1,000,000 copies/ml or 2×10 5 IU/ml), delivery modality did not impact MTCT.…”
Section: Active-passive Immunoprophylaxis With Hepatitis B Immunementioning
confidence: 99%
“…Expert opinion has suggested that there were insuffi cient data to recommend changes in the mode of delivery for HBV-infected women ( 104,105 ). Some more recent data support reconsideration of elective cesarean section to reduce MTCT including a metaanalysis that suggested a 17.5% absolute risk reduction compared with immunoprophylaxis alone.…”
Section: Active-passive Immunoprophylaxis With Hepatitis B Immunementioning
confidence: 99%
See 1 more Smart Citation
“…Pek çok çalışmada immünopro-filaksi başarısızlığı için en önemli risk faktörleri, annenin HBeAg pozitifliği ve yüksek HBV DNA düzeyi olarak bulunmuştur (4,12,13,15,(17)(18)(19)21,26,31) . Wang ve ark.…”
Section: Discussionunclassified
“…Ayrıca zor da olsa annenin meme başının etrafındaki çatlakların bulaş açısından risk yaratabileceği de bildirilmektedir (18) . Ancak çalışmalar, yeterli immünoprofilaksi uygulanmış çocuklarda emzirme ile beslenmenin mama ile beslenmeye göre daha yüksek risk oluşturmadığını göstermektedir (3,14,15,18,21,33) . Çin'de yapılan iki çalışmanın birinde doğum sonrası HBIG ve hepatit B aşılaması tamamlanmış 170 çocuktan emzirme ile beslenenlerde % 7, mama ile beslenenlerde % 6 oranında bulaş saptanmış.…”
Section: Discussionunclassified